Kinetic modelling for the photocatalytic degradation of phenol by using TiO2-coated glass raschig rings under simulated solar light - Maria J. Sampaio (2016)
BACKGROUNDImmobilisation of TiO2 photocatalysts has proven to be an efficient technological approach concerning both practical and economical aspects. The efficiency of photocatalytic phenol degradation using glass raschig rings coated with TiO2 Aeroxide((R))P25 was evaluated in a recirculation reactor operating under simulated solar light irradiation, by comparing the first order reaction rate (r) as a function of several operation conditions. RESULTSThe reaction rate increases with the initial phenol concentration ([PhOH](0)), the irradiation intensity (I), the number of TiO2-coated rings (N), and the hydrogen peroxide concentration [H2O2], and is minimally affected by the solution's flow rate (Q). A kinetic model was developed for the determination of the r as a function of the operating parameters. CONCLUSIONSThe empirical model allows the prediction of the efficiency of the photocatalytic degradation process in a wide range of operation conditions, which can be considered a useful tool for the scaling-up of the water treatment process. (c) 2014 Society of Chemical Industry